2016
DOI: 10.1016/j.bbapap.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of differentially expressed proteins in Yersinia enterocolitica-infected HeLa cells

Abstract: Yersinia enterocolitica is a facultative intracellular pathogen and a causative agent of yersiniosis, which can be contracted by ingestion of contaminated food. Yersinia secretes virulence factors to subvert critical pathways in the host cell. In this study we utilized shotgun label-free proteomics to study differential protein expression in epithelial cells infected with Yersinia enterocolitica. We identified a total of 551 proteins, amongst which 42 were downregulated (e.g. Prostaglandin E Synthase 3, POH-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Metabolomic studies identified changes in host metabolites upon S. Typhimurium infection, suggesting that metabolites of one of the groups, eicosanoids are elevated during infection in a murine model ( Antunes et al, 2011 ; Deatherage Kaiser et al, 2013 ). The eicosanoid pathway (Figure 1 ), which depends on the activity of cyclooxygenase (COX) enzymes ( Tanioka et al, 2000 ), is known to be affected by infections with bacterial pathogens ( Antunes et al, 2011 ; Deatherage Kaiser et al, 2013 ; Alugubelly et al, 2016 ). For instance, COX-2 is upregulated in murine macrophages infected with S. Typhimurium, which depends on the presence of the Salmonella Pathogenicity Island-2 (SPI-2) SpiC protein ( Uchiya and Nikai, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomic studies identified changes in host metabolites upon S. Typhimurium infection, suggesting that metabolites of one of the groups, eicosanoids are elevated during infection in a murine model ( Antunes et al, 2011 ; Deatherage Kaiser et al, 2013 ). The eicosanoid pathway (Figure 1 ), which depends on the activity of cyclooxygenase (COX) enzymes ( Tanioka et al, 2000 ), is known to be affected by infections with bacterial pathogens ( Antunes et al, 2011 ; Deatherage Kaiser et al, 2013 ; Alugubelly et al, 2016 ). For instance, COX-2 is upregulated in murine macrophages infected with S. Typhimurium, which depends on the presence of the Salmonella Pathogenicity Island-2 (SPI-2) SpiC protein ( Uchiya and Nikai, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…At the indicated time points, cells were washed, lysed with 0.1% Triton-X, diluted in sterile PBS, and plated on LB plates for CFU counts. A similar protocol was performed for Y. enterocolitica infection, based on our past work (Edelmann et al, 2010;Alugubelly et al, 2016).…”
Section: Gentamicin Protection Assaymentioning
confidence: 99%
“…Metabolomic studies identified changes in host metabolites upon S. Typhimurium infection, suggesting that metabolites of one of the groups, eicosanoids are elevated during infection in a murine model (Antunes et al, 2011;Deatherage Kaiser et al, 2013). The eicosanoid pathway (Figure 1), which depends on the activity of cyclooxygenase (COX) enzymes (Tanioka et al, 2000), is known to be affected by infections with bacterial pathogens (Antunes et al, 2011;Deatherage Kaiser et al, 2013;Alugubelly et al, 2016). For instance, COX-2 is upregulated in murine macrophages infected with S. Typhimurium, which depends on the presence of the Salmonella Pathogenicity Island-2 (SPI-2) SpiC protein (Uchiya and Nikai, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…DUBs are categorized into seven deubiquitinase sub-groups, including the ubiquitin-specific proteases (USPs), the ovarian tumor proteases (OTUs), JAB1/MPN/MOV34 metalloproteases (JAMMs), the ubiquitin C-terminal hydrolases (UCHs), the Josephins, the motif interacting with ubiquitin (MIU)-containing novel deubiquitinase family (MINDYs), and ZUP1 ( Komander et al., 2009 ). The ubiquitin-proteasome system plays a vital role in the host response to Gram-negative infections ( Lopez-Castejon and Edelmann, 2016 ), and previous studies have shown that bacterial pathogens can interfere with the deubiquitinase-mediated removal of ubiquitin modifications ( Kummari et al., 2015 ; Alugubelly et al., 2016 ; Hui et al., 2018 ). Concurrently, the host also regulates the activity and level of deubiquitinases to its advantage.…”
Section: Introductionmentioning
confidence: 99%